0653 Sleep Quality is Related to Observed Nighttime Agitation in Older Adults with Alzheimer's Disease and Restless Legs Syndrome. (12th April 2019) - Morrison, Janet D; Rangel, Angelica; Loera, Ana; Allen, Richard; Fry, Liam M; Chittams, Jesse; Rhodes, Joseph; Richards, Kathy
Abstract: Introduction: Nighttime agitation, also known as 'sundowning', is defined as the presence or worsening of behavioral disturbances (e.g., aggression, wandering) in the afternoon and/or evening. Nighttime agitation occurs in up to 66% of older adults with Alzheimer's disease, often leads to nursing home admission, yet effective treatments are few. We have shown that restless legs syndrome (RLS) is prevalent in older adults with Alzheimer's disease and nighttime agitation. Given the sleep loss and reduced iron status seen in RLS we sought to determine the relation of these variables to degree of agitation in these patients. Methods: Data were collected from 42 older adults (mean age 84.2 ± 7.5 years, 70% female) with Alzheimer's disease, RLS, and caregiver reported nighttime agitation behaviors. Participants were diagnosed with RLS using the validated Behavioral Indicators Test - Restless Legs. Participants' degree of agitated behaviors was based on the average of the Cohen-Mansfield Agitation Inventory (CMAI) scores obtained from two nights, Night 1 (5-10 pm) and Night 2 (10 pm-7am), of continuous direct observation by research assistants. Fasting morning blood samples were obtained to measure hemoglobin, serum ferritin, and transferrin saturation. Sleep time was the average minutes slept from 7-nights of wrist actigraphy (Micro-Mini Motionlogger). Results: Total minutes of sleep (mean 321.6 ± 152.2) and iron saturation (mean 26.2 ± 12.1) were correlated with frequency of nighttime agitation behaviors (mean 78.6 ± 40.6), r = -0.45, p < 0.01 and r = -0.34, p < 0.05, respectively. There was no significant relation between serum ferritin (p > 0.2) and CMAI scores. Conclusion: Data from this study provide evidence that sleep disturbances and iron levels should be investigated in older adults with Alzheimer's disease experiencing nighttime agitation behaviors. Diagnosis and treatment of iron deficiency and RLS may help reduce nighttime agitation, promote better sleep, and improve quality of life for older adults with Alzheimer's disease. Support (If Any): NIH-NIA R01AGO51588